2011
DOI: 10.1111/j.1365-2354.2011.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the training and support received by facilitators of a cancer education and support programme in New Zealand

Abstract: This study evaluates the training and support provided for facilitators who deliver the Living Well programme. This education and support programme, offered by the Cancer Society of New Zealand since 1991, aims to demystify cancer and its treatments, and develop self-efficacy of cancer patients and their supporters. A purposeful sample of 17 facilitators from five regions across New Zealand participated in semi-structured interviews. Quantitative data on demographics, qualifications and history with the progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The programme facilitators in the previous study (Jasperse et al . ) as well as participants in the current study have identified the need for better promotion of the LWCEP to cancer patients. Both these studies indicated that the programme is not well known outside those who deliver it or have taken part in it.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The programme facilitators in the previous study (Jasperse et al . ) as well as participants in the current study have identified the need for better promotion of the LWCEP to cancer patients. Both these studies indicated that the programme is not well known outside those who deliver it or have taken part in it.…”
Section: Discussionmentioning
confidence: 90%
“…Our previous evaluation of the LWCEP has shown that facilitators of the programme have the necessary background and training to fulfil their role (Jasperse et al . ). Both the CSNZ and the NZ healthcare system must work together to provide adequate support to cancer patients and their families.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and living well with cancer (Jasperse et al . ). Moreover, SEPs are not only delivered to clients but have been used to prepare staff to deliver educational programmes designed to improve health outcomes for patients (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…, Jasperse et al . ). The SERPS falls into the latter category as it was developed to prepare nurses and healthcare assistants to use reminiscence when caring for people with dementia.…”
Section: Introductionmentioning
confidence: 97%